2010
DOI: 10.2353/ajpath.2010.100399
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 2 Receptor Is an IFNγ-Inducible Microglial Protein that Facilitates Intracellular HIV Replication

Abstract: Insulin-like growth factor 2 receptor (IGF2R), also known as cation-independent mannose 6-phosphate (M6P) receptor, is a transmembrane glycoprotein localized in the trans-Golgi region and is involved in targeting both M6P-bearing enzymes and IGF2 to the lysosomal compartment. During development, IGF2R plays a crucial role in removing excess growth factors from both tissue and blood. Due to the perinatal lethality of the global Igf2r knockout, the function of IGF2R in adults, particularly in the CNS, is not kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 51 publications
(60 reference statements)
4
33
0
Order By: Relevance
“…Post-mortem brain sections with neuropathologic diagnosis of HIV encephalitis (HIVE) or minimal nonspecific changes (normal-appearing brains from both HIV+ and HIV− individuals) were obtained from the Manhattan HIV Brain Bank and processed for immunohistochemistry as previously described [29-31]. Briefly, sections were deparaffinized and underwent antigen retrieval in a citrate buffer at 95°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-mortem brain sections with neuropathologic diagnosis of HIV encephalitis (HIVE) or minimal nonspecific changes (normal-appearing brains from both HIV+ and HIV− individuals) were obtained from the Manhattan HIV Brain Bank and processed for immunohistochemistry as previously described [29-31]. Briefly, sections were deparaffinized and underwent antigen retrieval in a citrate buffer at 95°C for 20 min.…”
Section: Methodsmentioning
confidence: 99%
“…IGF1, IGF2, IGFBP2, and IGFBP3 levels are also altered in individuals with HIV infection [27,28]. We have also recently reported that IGF2R is highly upregulated in HIV-infected CNS and that IGF2R is a novel IFNγ-inducible microglial protein that functions as a positive regulator of HIV infection [29]. Given these provocative findings and the significant species-dependent differences in neuroinflammatory mechanisms, we examined the regulation of IGF1 and IGF2 expression in human microglia in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we recovered receptors and modulators that affect various signalling pathways, namely, T cell receptor subunits, Notch components and Hedgehog (HHIP) as well as factors involved in calcium signalling 35,36 . HIV-1 Env also associated with the mannose-6-phosphate/insulin-like growth factor receptor 2 (ILGF2), which is thought to facilitate HIV-1 replication in microglial cells 37 . The mannose-6-phosphate modification of gp120 being host-cell-line-specific, perhaps preferentially added to the viral envelopes of transmitted founder viruses 38 .…”
Section: The Env Interactomementioning
confidence: 99%
“…Microglial nodules seen in HIV encephalitis produce high levels of insulin-like growth factor receptor 2 (IGF2R), which is involved in intracellular HIV replication. When IGF2R expression is blocked by transfection with IGF2R siRNA, HIV production in microglia is decreased and IP-10 production is decreased [165]. …”
Section: Experimental Cerebral Malariamentioning
confidence: 99%